An analysis of our social structure as related to primitive civilizatons, patterns of culture. Anthropology, sociology, psichology, philosophy, brilliantly developed / Ruth Benedict - Benedict, Ruth
The science of custom, custom and behaviour, the child´s inheritance, our false perspective, reason for studying prmitive peoples; the diversity of culture, the cup of life, the necessity for selectio, adolescence and puberty as treated in differente societies, the integration of culture, all standards of behaviour patterning of culture, decline of the west, faustian and apollonian man, western civilization too intricate for study a detour via primitive tribes, the pueblos of new Mexico,, priests and masked gods, medicine societies, a strongly socialized culture, the middle road, fertility ceremonies, the northwest cpast of America, the nature of society, the individiual and the patterns of culture.